AKTIVITAS DAKWAH PENYULUH AGAMA ISLAM DI KECAMATAN SUNGAI AUR KABUPATEN PASAMAN BARAT - Edo Riyanto (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2024)
Dakwah is one of the most important things in the teaching of Islam. From the time of the Prophet to the present, Islam has not been freed from what is called Dakwah. By the presence of the gods, the religion of Islam spread all over the world. The Islamic activist is one of the examples of an activist who is an extension of the hands of the central government to the regions of Indonesia, without exception in the River Aur district of Western Pasaman. The leaders of Islam must be able to answer the problems that exist in the midst of society. This research uses qualitative methods with a descriptive approach. As a result of this research, the researchers found that in the implementation of Islamic activity, the Islamic religious authorities in the Aur River district refer to the Qur'an and Sunnah. The Islamic authorities have different tasks according to the specialists of each authority. But in the course of the day, the Muslims will be connected to each other. As for the forms of Islamic religious activism that exists in the River Aur district, among others: the blind extinction of the Qur'an, the family of the sacrilege, the assembly of taclim, zakat and waqaf, the dissemination of radicalism and the flow of blasphemy and others.